In-Wheel Motor Drive Systems for Electric Vehicles: State of the Art, Challenges, and Future Trends - Kritika Deepak; Mohamed Amine Frikha; Yassine Benômar; Mohamed El Baghdadi; Omar Hegazy (Energies, 2023)
Recently, there has been significant attention given to the electrification of transportation due to concerns about fossil fuel depletion and environmental pollution. Conventional drive systems typically include a clutch, reduction gear, and mechanical differential, which results in power loss, noise, vibration, and additional maintenance. However, in-wheel motor drive technology eliminates the need for these components, providing benefits such as higher system efficiency, improved wheel control, and increased passenger comfort. This article offers a comprehensive review of the technology and development of in-wheel motor drives. It begins with an overview of in-wheel motor drives in electric vehicles, followed by an exploration of the types of electric motors suitable for in-wheel motor drives. The paper then presents an industrial state of the art of in-wheel motors, comparing them with conventional motor drives, and reviews the implemented power electronics, control system, and cooling systems. Finally, the paper concludes by providing an outlook on the challenges and future trends of in-wheel drive systems.